(untitled) (AmeriQuests, 2012)
This manuscript addresses from a range of perspectives the crisis of capitalism, claiming that it’s failures are not an accident or a result of the actions of a few unprincipled men. Rather, it is a harbinger of things to come – loss of employment due to technology and globalization, a world without the myth of constant growth, tension between ethnic and national groups which seek to tilt the scale in favour of their group, a constant need for more radical technology and a fear of its unavoidable frightening side. Its one possible positive effect will occur if there emerges a new willingness to question the assumptions of capitalism and the political correctness of identity politics, shifts in both attitude and behavior that the author deems unlikely at the current juncture or in the foreseeable future. TABLE OF CONTENTS I. INTRODUCTION II. THE CURRENT CRISIS III. THE “SMALL GOVERNMENT” DEFENSE OF CAPITALISM IV. DOES THE HISTORY OF THE 20TH CENTURY VINDICATE CAPITALISM V. CAPITALISM AND SOVIET MARXISM VI. THE NEW MAN VII. INTERNATIONALISM AND GLOBALIZATION VIII. THE ALIENATED MAN IX. ALIENATION AND FAMILY STRUCTURE X. CAPITALISM AND DEMOCRACY XI. THE DOUBLETHINK OF CAPITALISM XII. CULTURE AND CAPITALISM XIII. THE “CONTRACT” DEFENCE OF CAPITALISM XIV. THE POSITIVE SIDE OF LIBERAL CAPITALISM XV. INSTITUTIONAL TAKE-OVER XVI. CAPITALISM AND THE TOWER OF BABEL XVII. THE NEW SYSTEM XVIII. POLITICAL STRUCTURE IN THE NEW SYSTEM XIX. THE NEW SYSTEM AND INDIVIDUAL HAPPINESS XX. COURTS AND JUDICIAL REVIEW IN THE NEW SYSTEM XXI. PHILOSOPHY, SCIENCE AND MORALITY IN THE NEW SYSTEM XXII. WHY NOT “REAL” SOCIALISM XXIII. HOW IS A NEW SYSTEM TO BE CREATED XXIV. EDUCATION XXV. DISOBEDIENCE AND WITHDRAWAL XXVI. REFORM OF THE LEFT XXVII. LABOUR UNIONS AS A SPECIAL INTEREST LOBBY XXVIII. MULTICULTURALISM AND CULTURE XXIX. CULTURE AND DEMOGRAPHY XXX. A BOOT IN THE FACE OF MANKIND FOREVER XXXI. CONCLUSION